Wet peroxide oxidation over Cu-ZSM-5 and Fe-ZSM-5 catalysts. Kinetics study in batch and flow reactors; XXI International Conference on Chemical Reactors "CHEMREACTOR-21", Delft, The Netherlands, September 22-25, 2014 - Taran O. P.; Zagoruiko A. N. Andrey Nikolaevich; Ayusheev A. B.; Yashnik S. A.; Prihod'ko R. V.; Goncharuk V. V.; Ismagilov Z. R.; Parmon V. N. (2014, 2014)
Title screen